Comments on fanfiction: collaborative written production on the internet - Almeida Lara, Marina Totina de [UNESP]; Mendonca, Marina Celia [UNESP] (Editora Univ Pontificia Univ Catolica Rio Grande Sul-edipucrs, 2021)
This article aims to analyze the relation of alterity, based on Bakhtin's proposition, in readers' comments on fanfiction published on the Brazilian website Spirit Fanfics e Historias. Fanfiction is a fictional story written individually or collabo- ratively as of books, series, movies and/or characters by other authors. Such texts run on the internet within specific communities - websites created with this purpo- se, such as the one previously mentioned - and this space of written production is a place where writers and readers engage in a dialog about their productions, through comments, aiming to perfect them according to what is valued in such spaces. To this end, the act of commenting on somebody else's production, showing one's own positioning, in order to collaborate with the development of the text, is fundamental, Thus, based on Bakhtin, Volochinov and the Dialogical Discourse Analysis, this work analyzes the relations of alterity in five comments posted on fanfiction about the series 13 Reasons WhyThe chosen methodology - the com- parison - consists of relating texts, aiming to broaden contexts to understand the utterances, as proposes Bakhtin. From the Bakhtinian proposition, we point the concepts of architectonics, dialog, concrete utterance, activity sphere and alterity as relevant to the current discussion. We started from the hypothesis that the relations of alterity are key elements for the edification of these texts within this collaborative community of written production. At that, the reached results indicate that the comment is a component of the fanfiction, which guides the production according to the relation of alterity between authors and readers. Furthermore, the article highlights the importance of the genre comment to this relation, which appeared to be, according to the analyses, unique in this space, with relationships between me and other shown in its architectonics. Finally, this article adds to the area of Bakhtinian studies regarding the discourse genres in digital context.
Keywords: Dialogical Discourse Analysis; Bakhtin Circle; Fanfiction